PROBLEMATICS OF TEACHING DRAMA IN RURAL ELEMENTARY SCHOOLS: A PERSPECTIVE FROM MADURA - Ach Fauzi (STKIP Citra Bakti, 2026)
This study examines drama-based literary learning at the elementary school level in rural schools in Madura, focusing on teachers’ perspectives. This research employed a qualitative descriptive approach, collecting data through in-depth interviews with elementary school teachers who integrate drama into English language learning. The data were analyzed thematically to identify patterns related to instructional processes and obstacles faced by teachers. The findings reveal that drama learning is implemented inconsistently and lacks systematic planning. Teachers mainly use methods such as reading and analyzing scripts, role-playing, and limited improvisation. However, several interrelated challenges hinder effective implementation, including limited instructional time, inadequate facilities and learning resources, low teacher confidence and competence in drama pedagogy, and students’ low motivation and anxiety about performing activities. These challenges indicate a gap between the pedagogical potential of drama and its practical realization in rural elementary schools. The study concludes that effective drama-based learning requires contextual and adaptive instructional strategies, professional development programs focused on drama pedagogy, and supportive learning environments that promote psychological safety for students. Future research is recommended to develop practical drama learning models and training programs tailored to rural school contexts.